The Role of Contextual Socioeconomic Circumstances and Neighborhood Poverty Segregation on Mortality in 4 European Cities. (October 2017) - Marinacci, Chiara; Demaria, Moreno; Melis, Giulia; Borrell, Carme; Corman, Diana; Dell'Olmo, Marc Marí; Rodriguez, Maica; Costa, Giuseppe
Several studies have recognized the health disadvantage of residents in socioeconomically deprived neighborhoods, independent of the influence of individual socioeconomic conditions. The effect of neighborhood socioeconomic deprivation on general mortality has appeared heterogeneous among the cities analyzed: the underlying mechanisms have been less empirically explored, and explanations for this heterogeneous health effect remain unclear. The present study aimed to: (1) analyze the distribution of socioeconomically disadvantaged persons in neighborhoods of 4 European cities—Turin, Barcelona, Stockholm and Helsinki—trying to measure segregation of residents according to their socioeconomic conditions. Two measuring approaches were used, respectively, through dissimilarity index and clustering estimated from Bayesian models. (2) Analyze the distribution of mortality in the above mentioned cities, trying to disentangle the independent effects of both neighborhood socioeconomic deprivation and neighborhood segregation of residents according to their socioeconomic conditions, using multilevel models. A significantly higher risk of death was observed among residents in more deprived neighborhoods in all 4 cities considered, slightly heterogeneous across them. Poverty segregation appeared to be slightly associated with increasing mortality in Turin and, among females and only according to dissimilarity, in Barcelona. Few studies have explored the health effects of social clustering, and results could inform urban policy design with regard to social mix.